1984
DOI: 10.1021/bi00297a023
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metal ions on the phase properties of phosphatidic acid in combination with natural and synthetic phosphatidylcholines: an x-ray diffraction study using synchrotron radiation

Abstract: Synchrotron radiation was used as an X-ray source of extreme brilliance to investigate by X-ray diffraction the phase behavior of fully hydrated unoriented samples of egg phosphatidic acid (egg PA) in combination with egg phosphatidylcholine (egg PC), dimyristoylphosphatidylcholine (DMPC), or dipalmitoylphosphatidylcholine (DPPC). The diffraction method was sensitive to greater than or equal to 2 mol % gel and greater than or equal to 30 mol % liquid-crystal phase lipid. Accordingly, the liquidus boundary was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
30
0

Year Published

1986
1986
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 46 publications
9
30
0
Order By: Relevance
“…1) in the presence of EPA, evident in the gel phase. In our experi-37 mental conditions a complete miscibility of DMPC and EPA is suggested by anisotropy data, in agreement with Caffrey and Feigenson [25]. As for DPH, TMA-DPH fluorescence decay requires at least two exponentials for adequate description.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…1) in the presence of EPA, evident in the gel phase. In our experi-37 mental conditions a complete miscibility of DMPC and EPA is suggested by anisotropy data, in agreement with Caffrey and Feigenson [25]. As for DPH, TMA-DPH fluorescence decay requires at least two exponentials for adequate description.…”
Section: Discussionsupporting
confidence: 85%
“…4). The anisotropy values for DMPC/EPA show that in the mixture, the transition was shifted to lower temperature and the transition range was broader (15--22°C) in agreement with data reported by Caffrey and Feigenson [25]. Moreover, above and below the DMPC/EPA transition, the anisotropy was higher than that observed in the corresponding phases for pure DMPC.…”
Section: Tma-dph Fluorescence In Dmpc and Dmpc/epa Liposomessupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, addition of NaCl reduced the T m of the cell membrane and increased the pressure required to induce a phase transition from the liquid crystalline phase to the gel phase. Monovalent cations do not affect the phase properties of phospholipid bilayers (6). Therefore, the protective effect of NaCl on the cell membrane of L. lactis must be attributed to the presence of compatible solutes accumulated intracellularly.…”
Section: Discussionmentioning
confidence: 94%
“…Differential scanning calorimetry (DSC) measurements revealed that the phase-transition temperature of the DPPC vesicles (T c 38 8C) [12] was not influenced by incorporation of Rh-5 and Mn-1 (vide infra).…”
Section: Resultsmentioning
confidence: 99%